Proceedings of the 5th ACM International Conference on Collaboration Across Boundaries: Culture, Distance &Amp; Technology 2014
DOI: 10.1145/2631488.2631499
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in how an engagement-seeking robot should approach a group of people

Abstract: In our daily life everything and everyone occupies an amount of space, simply by "being there". Edward Hall coined the term proxemics for the studies of man's use of this space. This paper presents a study on proxemics in Human-Robot Interaction and particularly on robot's approaching groups of people. As social psychology research found proxemics to be culturally dependent, we focus on the question of the appropriateness of the robot's approach behavior in different cultures. We present an online survey (N=18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Significant effects have been found in various settings; in different contexts [6], with different properties of the robot [7], with relation to the background of the participants [8], and for different cultures [9]. These findings show that taking proxemics and F-formations into account can have a positive effect on the perceived appropriateness of the displayed robot behavior.…”
Section: A Social Positioning In Roboticsmentioning
confidence: 89%
“…Significant effects have been found in various settings; in different contexts [6], with different properties of the robot [7], with relation to the background of the participants [8], and for different cultures [9]. These findings show that taking proxemics and F-formations into account can have a positive effect on the perceived appropriateness of the displayed robot behavior.…”
Section: A Social Positioning In Roboticsmentioning
confidence: 89%
“…The results of an online survey (N=181), which was distributed to people in China, the U.S.A. and Argentina (see Fig. 7(a)), show that participants prefer a robot that stays out of their intimate space zone just like a human would be expected to do (Joosse et al, 2014). However, Chinese participants accepted closer approaches than people from the U.S.A. and Argentinia.…”
Section: User Studies and Contextual Analysismentioning
confidence: 99%
“…It is an established fact that robots are generally treated by people as social actors and expected to comply with social norms [6]. As an example, two different studies on the interpersonal distance between a person and a robot report that people (i) mostly conform to Hall's social zones when approaching a robot, thus acknowledging it as a social actor [7] and (ii) prefer a robot that stays out of people's intimate space zone, thus expecting it to behave as a sociallycompetent actor [8]. A study on the acceptability of a robot navigating a human environment found that a robot programmed to respect four basic social conventions was preferred over one lacking this knowledge [9].…”
Section: B Cultural Competence In Robotics Until Todaymentioning
confidence: 99%